2015
DOI: 10.17219/pzp/60919
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Consumption of Selected Foods Among the Students of the University of Applied Science in Nysa Regarding the Implementation of Rational Nutrition Recommendations

Abstract: A -koncepcja i projekt badania; B -gromadzenie i/lub zestawianie danych; C -analiza i interpretacja danych; D -napisanie artykułu; E -krytyczne zrecenzowanie artykułu; F -zatwierdzenie ostatecznej wersji artykułu StreszczenieWprowadzenie. Niewłaściwy sposób żywienia wpływa zarówno na obecny stan zdrowia studentów, jak i determinuje stan ich zdrowia w przyszłości. Znaczącą rolę w zachowaniu zdrowia odgrywa styl życia, a zwłaszcza sposób odżywiania. Podejmowanie badań nad zachowaniami żywieniowymi młodzieży akad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…Among BUT students, such people constituted only less than 2%. Similar results, excluding University of Bialystok students, were observed by Misiarz et al—medical faculties (18.1%) and non-medical (2.8%), and Grochowska-Niedworok et al—medical faculties (10.85%) and non-medical faculties (5.25%) [ 23 , 30 ]. In turn, in a study by Kowalcze et al, a small percentage of dietetics students refrained from eating this type of food (7%) [ 24 ].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Among BUT students, such people constituted only less than 2%. Similar results, excluding University of Bialystok students, were observed by Misiarz et al—medical faculties (18.1%) and non-medical (2.8%), and Grochowska-Niedworok et al—medical faculties (10.85%) and non-medical faculties (5.25%) [ 23 , 30 ]. In turn, in a study by Kowalcze et al, a small percentage of dietetics students refrained from eating this type of food (7%) [ 24 ].…”
Section: Discussionsupporting
confidence: 81%
“…Mahfouz et al showed that 14.9% of medical students and 13.3% of non-medical students resigned from drinking soft drinks [ 31 ]. In the research conducted by Misiarz et al the right behavior in this respect among students was significantly lower, as 23.35% of medical students and 9.56% of non-medical students declared that they did not drink carbonated drinks [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations